Writing Security : United States Foreign Policy and the Politics of Identity. - Campbell, David (University of Minnesota Press, 1998)
In this new edition of a groundbreaking work, David Campbell provides a fundamental reappraisal of American foreign policy, with a new epilogue to address current world affairs and the burgeoning focus on culture and identity in the study of international relations.